Factors contributing to activity limitations in Leprosy patients in Sitanala Leprosy Village, Indonesia - Anandika Pawitri; Sri Linuwih Menaldi; Melani Marissa (Galenos Publishing House, 2022)
Background and Design: To investigate the association between sociodemographic variables, illness duration, leprosy types, comorbidities, and World Health Organization disability grading system for leprosy with daily activity limitations in people with leprosy who had completed multidrug therapy. Materials and Methods: A cross-sectional study was conducted in Sitanala Leprosy Village, Tangerang, Indonesia, in April 2018. Sociodemographic data and leprosy baseline characteristics were obtained from patients with leprosy who had completed multidrug therapy. The Screening of Activity Limitation and Safety Awareness scale was used to measure limitations in performing daily functional activities. Results: A total of 205 people were included in the study, of which 39 (19%) had eye disabilities, 178 (86.8%) had hand disabilities, and 187 (91.2%) had foot disabilities. A total of 135 (65.8%) people had mild-to-moderate functional limitation, and 33 (16%) had severe-to-very severe functional limitation. The proportion of unemployed individuals was higher among those with severe-extreme limitation compared to those without significant limitation (p=0.01). Individuals with eye disability had a higher risk of having severe-extreme activity limitation compared to those without eye disability (p=0.008). A dose-response association of hands and foot disabilities with activity limitation was found; the adjusted odds ratio (OR) of the association of hands and foot disabilities with mild-moderate activity limitation was 3.03 (p=0.012), and the association was greater with severe-extreme activity limitation (adjusted OR; 20.38, p=0.006). Conclusion: Severe disability is associated with functional activity limitations. The findings of the present study can guide healthcare providers in designing appropriate prevention and intervention services for patients with leprosy-related disabilities.